The Comparison of Hemoglobin Levels, Blood Oxygen Saturation, and Breaths Frequency on The Lowlander and Highlander - Syamsul Bahri; Lalu Hasan Nasirudin Zohri; Istiqomah Istiqomah; M. Y. Yusuf; Hendra S. Putra (Jurnal Biologi Tropis, 2022)
Geographical conditions affect human physical and physiological conditions, one of the examples is the height of residence that can make the respiratory system different among population groups. This study aims to compare the respiratory system between highlanders and lowlanders in terms of hemoglobin levels, blood oxygen saturation, and breaths frequency. The research model used was a comparative study with a purposive sampling method based on: age criteria with a range of 16-19 years, a minimum of 6 months stayed at the research location, and there is no recorded respiratory system disease. Data analysis used was independent t-test with Shapiro-Wilk prerequisite test for normality and one-way ANOVA for homogeneity, then Mann-Whitney test for follow-up non-parametric test. The results showed that the highlanders generally have oxygen saturation and hemoglobin levels with an average value of 98.81% and 14.69g/dL higher than those in the lowlands with a value of 97.86% and 13.14g/dL. On the other hand, the average value of breath frequency of highlanders is 17.38/minute which tends to be lower than that of lowlanders with 24.17/minute. The prerequisite test showed highlanders oxygen saturation data that were not normally distributed with a significance value of 0.003, then oxygen saturation data and breath frequency were not homogeneous with a significance value of 0.000 and 0.003 respectively. The comparative test showed a significance value of 0.002 for hemoglobin through independent t-test, then obtained asymptomatic significance values ​​of 0.004 and 0.000 for oxygen saturation and breaths frequency through the Mann-Whitney test. Based on the significance value obtained, it can be stated that there are significant differences in hemoglobin levels, oxygen saturation, and breaths frequency per minute between highland and lowland residents. It is recommended to conduct further research on lung capacity and chest cavity index to provide a more holistic explanation of the differences in the respiratory system between highland and lowland residents.